Quaternion Based Fuzzy Neural Network Classifier for MPIK Dataset's View-invariant Color Face Image Recognition (Informatica, 2025)
Quaternion Based Fuzzy Neural Network Classifier for MPIK Dataset's View-invariant Color Face Image Recognition